Result of plum growth development of different plum varieties in Altai region - Saikhantsetseg, N; Ninj, B (Mongolian Journal of Agricultural Sciences, 2014)
Due to global warming and Mongolian climate change air temperature has increased by 1, 56 degree in last 60 years. 25 percent of desertification covers once in 2-3 years whereas more than 50 percent of desertification occurs once in 4-5 years in Mongolian territory. Dust storm increased 3-4 times in Gobi and step regions in comparison to 1960s (Desertification UB 2009). Studying perennial trees, bushes and fruit tree cultivation, its adaptability and yield increasement is a stable way to reduce desertification, restore land degradation, increase yield and improve soil fertility. Plum is easily adaptable plant to cultivate in any type of soil and climate of Mongolia. Plum specificities are highly adaptable, yields in short period after planting, tolerant during winter, disease infected condition is comparably low, later uses of plum fruits are diverse and economically valuable. Plum is also planted for medicinal and ornamental use. Increasing interests and demand on making home garden and to plant diverse of fruit trees are primary reason to conduct this study. Experiment was done in Khovd branch of Agricultural State University in fruit experimental station. DOI: http://dx.doi.org/10.5564/mjas.v11i2.224 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.83-86